Factors affecting the value and price of cryptocurrencies : a systematic review of the scientific literature - Mamanova, Dana (2024)
Not long-ago cryptocurrency was a topic that only a small group of tech enthusiasts was interested in; however, it experienced a lightning-fast rise in popularity and value over the past decade. With this rapid growth and significant volatility, understanding the determinants of this digital asset's price has become important for investors, policymakers, and researchers. The surge in popularity has been accompanied by an exponential growth in scientific literature, making it hard to navigate this emerging field. This diploma thesis employs a systematic literature review methodology to identify and analyze the factors affecting the value and price of cryptocurrencies, as it is crucial for researchers to understand the state of knowledge and the potential gaps for further development of the field. The findings reveal that empirical studies in the field lack the theoretical background and concentrate more on developing price prediction models and analyzing the random bunch of different variables rather than exploring the causalities between variables and cryptocurrencies’ price development. Moreover, the majority of researchers favors quantitative over qualitative methods, resulting in limited methodological diversity and leaving blind spots like investors’ behavior and motivation. Additionally, most studies are still Bitcoin-centred, which may negatively affect our understanding of other cryptocurrencies' value drivers. In conclusion, while cryptocurrencies have the potential to transform the financial sector, there are still many gaps to be filled to reach a better understanding and ensure the sustainable development of the field.